Solution validator and visualizer for (combined) vehicle routing and container loading problems - Corinna Krebs; Jan Fabian Ehmke (Annals of Operations Research, 2023)
The optimization of cargo loading and transportation are two highly considered optimization problems (namely "3L-CVRP"). The combination of both has attracted increasing interest in the past decades. Hereby, 2D or 3D items have to be transported from one depot to a given set of customers using a homogeneous fleet of vehicles. Each route must be provided with a feasible packing plan taking various constraints into account. Combining the two optimization problems increases the complexity of the solution approaches, leading to a higher difficulty to check the results for correctness. To support the research progress and to enable transparency of solution structures, this paper provides an overview of recent literature, problem formulations, and best-known solutions. Furthermore, we introduce two open-source tools: The "Solution Validator" checks the feasibility of solutions in terms of considered constraints. The "Visualizer" provides two views and visualizes solutions. In the vehicle routing view, the tour plan and the corresponding schedule are displayed. In the loading view, the position of each item in the cargo space is demonstrated. In both views, it is possible to check the feasibility of the solution and highlight violated items. Besides the combined problem, the tool can be used also for one optimization problem (e.g. vehicle routing problem or container loading). The source codes for both tools are available at GitHub in C++ and Java and can be easily integrated into other researchers' code.
Keywords: 000; Open source tools; Vehicle routing problem; Container loading problem